The late chromatoid body component TSSK2 is involved in translational regulation in elongating spermatids in mice - Lehti, Mari S.; Ma, Lin; Kärnä, Salli; Laasanen, Samuli; Ahmedani, Ammar; Olotu, Opeyemi; Bourgery, Matthieu; Tran, Panyi; Sironen, Anu; Kotaja, Noora (Bioscientifica, 2025)
Spermatogenesis culminates in a dramatic morphological transformation, including a tight compaction of the chromatin and nuclear reshaping that largely silences transcription. Due to transcriptional silencing, the production of sperm-specific proteins needed for the morphological transformation requires active storage and translational regulation of mRNAs transcribed in earlier cell types. The germline-specific ribonucleoprotein (RNP) granule, the chromatoid body (CB), accumulates RNAs and has a role in RNA regulation in early haploid cells (round spermatids). In late haploid cells (elongating spermatids), the CB is transformed into the so-called late-CB, whose function in RNA regulation has remained elusive. Here we characterized the function of the late-CB by identifying proteins and RNAs interacting with the known late-CB marker, testis-specific serine/threonine-protein kinase 2 (TSSK2). We showed that TSSK2 and the late-CB associate with translation initiation factors and ribosomal proteins. Furthermore, we revealed an association of TSSK2 with a specific set of mRNAs that are enriched in polysome fractions in elongating spermatids, supporting the role of the late-CB in temporally regulated translation. These results link the function of the late-CB to RNA regulation during late spermatogenesis for the first time, providing important novel information about the RNA regulatory processes required for spermatogenesis and male fertility.
Keywords: spermatogenesis; male fertility; elongating spermatids; RNP granules; translation; chromatoid body; TSSK2